Penerapan Pembelajaran Logika Fuzzy pada Robot Penghindar Rintangan - Renny Maulidda; Selamat Muslimin; Hidayati Ami (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
The design of the obstacle avoidance robot prototype uses the fuzzy logic control method which is made for learning facilities and implementing intelligent systems. This obstacle avoidance robot can be applied to a security system, which is effective in providing safety for drivers and passengers of motorized vehicles, because this robot is designed to avoid all obstacles in its path. This obstacle avoidance robot is designed based on an Arduino Uno microcontroller with navigation using an ultrasonic sensor HC-SR04 attached to a servo motor. The actuators used are 2 DC motors and programming using Arduino software by implementing fuzzy logic control to measure the distance read by the sensor and the robot can determine the direction of the next movement. So that after testing, the results obtained that the robot can be implemented as expected.